El cuento de los Hermanos Grimm «El Rey rana o Enrique-el-férreo»: recepción del lectorado infantil y de los enseñantes en España. Propuestas para la enseñanza desde una perspectiva de género. - Luengo Gascón, Elvira (Ondina - Ondine, 2018)
In this article, results are shown from the research project carried out in different Spanish schools with respect to reception of the children’s tale, “The Frog Prince”. The collective imagination doesn’t make an impact just on girls, boys, and their teachers, but also university students. The analysis encompasses reader reaction on these three levels, along with stereotypes from a gender perspective and proposals by teachers for a literary education through fairy tales. Does the princess’s reaction constitute an act of submission or one of rebellion? Finally, the personal experience of reading is what builds literary learningKey Words: «The Frog King or Iron Henry», The Brothers Grimm, literary conversation, didactic proposals with a gender-based perspective.